Teacher Professional Development in Learning Communities: Pathways to Inclusive Education (Revista Lusófona de Educação, 2025)
Teacher professional development within the context of learning communities is a central theme inInclusive Education, highlighting the need to deepen the role of these communities in the sharing of strategies,critical reflection, and co-construction of inclusive practices. Therefore, our objective is to identify teachers’ perspectiveson the challenges and opportunities for learning and professional development in the workplace, andto characterise their experiences of participation in such communities. This descriptive-correlational quantitativestudy involved the administration of an online questionnaire to 102 professionals aged between 31 and 65 years(50.8±10.2), from preschool, primary and secondary education, 79 of whom were female. Internal consistencywas confirmed (α=.96), and the exploratory factor analysis indicated a four-factor solution explaining 46% of thetotal variance. The results show that teachers value continuous professional development for personal growthand improvement of pedagogical practices; they recognise the importance of school leadership and collaborativeculture in fostering their professional development; and they see participation in learning communities askey to promoting equitable practices. The effective implementation of such communities in schools depends onthe creation of support structures, effective leadership, and a culture focused on lifelong learning that promotesprofessional development.Keywords: Learning Communities; Collaborative Culture; Teacher Professional Development; Inclusive Education; Inclusive Pedagogical Practices